Effect of eicosapentaenoic acid, docosahexaenoic acid, and their combination on selected atherogenic biomarkers in a high-fat diet rat model - Amal H. Abu Sadah, Reem Issa, Husni Farah, Ghaleb Oriquat, Shady H. Awwad, Ibrahim Mosleh, Beisan A. Mohammad, Ahmad Aljaberi, Mohammad Al-Najjar, Mahmoud S. Abu-Samak (Journal of Applied Pharmaceutical Science, 2025)
Findings concerning eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) as well as omega-3 (n-3FA) effects on lipid profile and biomarkers of atherosclerosis progression are still highly debated. The current study was designed to evaluate and compare the effect of EPA, DHA, and their combination in the form of n-3FA on serum non-high-density lipoprotein (NHC), oxidized-low-density lipoprotein (Ox-LDL), Lipoprotein(a) Lp(a), and other lipid profile parameters levels in rats with high-fat diet model. Based on the diet and supplementation model, six groups (n = 6 per group) of male Westar rats were distributed as follows: standard diet (SD), high-fat diet (FD); FD + atorvastatin (ATV), FD + omega-3 (n-3FA), FD + EPA (EPA), and FD + DHA (DHA). The results have shown a significant higher mean NHC levels in the DHA and n-3FA groups than in the EPA group (27.52 ± 2.92 vs. 43.23 ± 8.98 and 45.65 ± 5.08 mg/ dl, respectively, p < 0.001). In addition, the mean levels of total cholesterol and Lp(a) levels were significantly higher in DHA than in EPA (35.8 ± 2.04 vs. 51.8 ± 6.33 mg/dl, 2.42 ± 0.71 vs. 4.41 ± 1.14 ng/dl, p < 0.001). Significant higher mean Ox-LDL levels were observed in n-3FA than in DHA (p < 0.001) or EPA (p < 0.05). No significant in mean Ox-LDL levels was observed between EPA and DHA study groups (t = 3.62, p = 0.1387). The current study findings revealed the potential advantages of EPA supplements but not DHA supplements alone or their combination with EPA in the common form known as omega-3 for preventing or treating hyperlipidemia.
Keywords: Omega-3, DHA, EPA, Ox-LDL, non-HDL, lipid profile, lipidemia